Managing Improvement in Healthcare Attaining, Sustaining and Spreading Quality (Organizational Behaviour in Healthcare,, 2018)
Reflecting the challenges and opportunities of achieving improvement in healthcare systems, the contributions of this innovative new text lend depth and nuance to an increasing area of academic debate. Encompassing context, processes and agency, Managing Improvements in Healthcare addresses the task of attaining, embedding and sustaining improvement in the industry. The book begins by offering insight into the different valued aspects of quality, providing specific examples of national and organizational interventions in pursuit of improvement. The second part focuses on strategies for embedding good practice and ensuring the spread of high quality through knowledge mobilization, and the final part draws attention to the different groups of change agents involved in delivering, co-creating and benefitting from quality improvement. This inventive text will be insightful to those researchers interested in healthcare and organization, looking to transform theory into policy and practice.